Advanced oxidation protein products — biological marker of oxidative stress = Zaawansowane produkty utleniania białek – biologiczne markery stresu oksydacyjnego - Cwynar, Anna; Olszewska-Słonina, Dorota; Czerniak, Bartosz; Źyła, Magdalena (Journal of Education, Health and Sport, 2016)
Cwynar Anna, Olszewska-Słonina Dorota, Czerniak Bartosz, Źyła Magdalena. Advanced oxidation protein products — biological marker of oxidative stress = Zaawansowane produkty utleniania białek – biologiczne markery stresu oksydacyjnego. Journal of Education, Health and Sport. 2016;6(9):597-603. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.155059 http://ojs.ukw.edu.pl/index.php/johs/article/view/3885 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016. Advanced oxidation protein products — biological marker of oxidative stress Zaawansowane produkty utleniania białek – biologiczne markery stresu oksydacyjnego Anna Cwynar1, Dorota Olszewska-Słonina1, Bartosz Czerniak1, Magdalena Źyła2 1 Katedra Patobiochemii i Chemii Klinicznej, Collegium Medicum w Bydgoszczy 2 Katedra Psychiatrii, Collegium Medicum w Bydgoszczy ABSTRACT Advanced oxidation protein products (AOPPs) are mostly derivatives of oxidatively modified albumin. The results of many experimental studies confirm intensification of oxidative modifications of proteins and an increase in concentration of advanced oxidation protein products (AOPPs) in different pathological conditions, particularly those with well documented involvement of oxidative stress in their etiopathogenesis, but also those where its role is not yet well understood. Currently intensive research is carried out on the possibility of using AOPPs as useful indicators for diagnosing, prognosis and monitoring of diseases. Keywords: advanced oxidation protein products, autoimmune disease, oxidative stress STRESZCZENIE Zaawansowane produkty utleniania białek (AOPPs), to najczęściej pochodne zmodyfikowanej oksydacyjnie albuminy. Wyniki licznych badań doświadczalnych potwierdzają nasilenie oksydacyjnych modyfikacji białek i wzrost stężenia zaawansowanych produktów utleniania białek (AOPPs) w różnych stanach patologicznych, szczególnie tych o dobrze udokumentowanym udziale stresu oksydacyjnego w ich etiopatogenezie, ale także takich, w których jego rola nie jest jeszcze dobrze poznana.. Obecnie trwają intensywne badania nad możliwością wykorzystania AOPPs, jako użytecznych wskaźników do diagnozowania, prognozowania oraz monitorowania chorób. Słowa kluczowe: zaawansowane produkty utleniania białek, choroby autoimmunologiczne, stres oksydacyjny